Seismic Response Analysis of Transmission Tower-Line System on a Heterogeneous Site to Multi-Component Spatial Ground Motions - Bai, F.; Hao, Hong; Bi, Kaiming; Li, H. (Multi-Science Publishing, 2011)
This paper studies the nonlinear responses of a coupled transmission towerline system on a heterogeneous site subjected to multi-component spatially varying ground motions. The three-dimensional finite element model of the transmission tower-line system is established with consideration of the geometric nonlinearity of the transmission lines. The spatial variation of ground motions associated with the wave passage, coherency loss and local site effects are considered. The spatial ground motions on ground surface are derived by modelling the base rock motion propagating through the local soil sites. The base rock motions are assumed consisting of out-ofplane and in-plane waves and are simulated stochastically based on an empirical coherency loss function and the filtered Tajimi-Kanai power spectral density function. The effects of multi-component, spatial variations of ground motions and varying site conditions at multiple tower foundations on seismic response of the transmission tower-line system are analysed. The study reveals that for a reliable seismic response analysis and safe and economic seismic resistance design of transmission tower-line systems, the multi-support and multi-component earthquake excitations with consideration of the effects of local site conditions on ground motion spatial variations should be considered.